Partnership Formation for Change: Indicators for Transformative Potential in Cross Sector Social Partnerships - Seitanidi, Maria May (Journal of business ethics, 2010)
We provide a grounded model for analysing formation in cross sector social partnerships to understand why business and nonprofit organizations increasingly partner to address social issues. Our model introduces organizational characteristics, organizational motives and history of partner interactions as critical factors that indicate the potential for social change. We argue that organizational characteristics, motives and the history of interactions indicate transformative capacity, transformative intention and transformative experience, respectively. Together, these three factors consist of a framework that aids early detection of unnecessary partnering efforts and provide indicators of partners’ transformative potential. Further we discuss the reciprocal, multi-level nature of change in social partnerships through the interplay between the organizational, individual and social levels of reality. The formation stage of partnerships contributes to the partnership and corporate social responsibility (CSR) literatures a deep understanding of the organisations’ early interactions by placing within a historical context that reveals their dynamics and their potential to deliver organisational and social change.